The Analysis of the Song Lyrics of the Energy of Asia Music Album from the Perspective of Systemic Functional Grammar - Septyana Atik Purwandari; Didin Nuruddin Hidayat; Waliyadin Waliyadin; Muhammad Syafii S (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
Music has played a role as the media in modern society. It is used not only to be listened to accompany in doing activities but also as the media to inform people about what is happening around them. This study aims to investigate the most frequent occurrence of mood system and adjunct of each lyric and describe the modality realized in the lyric of Energy of Asia’s album of the 2018 Asian Games, to find the transitivity processes, and to find the textual meaning (theme) of the song lyrics. In this descriptive qualitative research, three song lyrics from the "Energy of Asia" music album released in 2018 were selected, including nonpolitical Asian dance, unbeatable, and dance tonight. The analysis of the data involved some activities, including listening to the songs, finding the printed lyrics of the songs, analyzing the clauses based on the mood residue elements, describing the most frequent used-mood types, seeing the modality finite and mood adjunct, finding the transitivity process, and the textual meaning occurred on the song lyrics and making a conclusion. This paper attempts to reveal how the perspective of Systemic Functional Grammar (SFG) is employed to analyze song lyrics. The result of this study showed that the message in the lyrics is mostly about the pride of being Indonesian people in celebrating the Asian Games and motivating the players to be the winner in this event.